2018
DOI: 10.3847/1538-4357/aabad8
|View full text |Cite
|
Sign up to set email alerts
|

Dense Gas, Dynamical Equilibrium Pressure, and Star Formation in Nearby Star-forming Galaxies

Abstract: We use new ALMA observations to investigate the connection between dense gas fraction, star formation rate, and local environment across the inner region of four local galaxies showing a wide range of molecular gas depletion times. We map HCN (1-0), HCO + (1-0), CS (2-1), 13 CO (1-0), and C 18 O (1-0) across the inner few kpc of each target. We combine these data with short spacing information from the IRAM large program EMPIRE, archival CO maps, tracers of stellar structure and recent star formation, and rece… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
148
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(181 citation statements)
references
References 116 publications
29
148
4
Order By: Relevance
“…The lines in the plots are Local Polynomial Regression fits only to guide the eye, which is similar to the binning method used in many other studies, and they do not strongly suggest that our data points closely follow those fits. This is consistent with Usero et al (2015) and the larger galaxy sample compiled by Gallagher et al (2018a), where they show a very weak correlation (ρ sp = 0.13) and a large scatter about the relationships, and they suggest that the HCN/CO ratio is a relatively poor predictor of SFE mol . Our plot shows a similar case using high-J dense molecular lines, implying that the SFE, if measured as SFR per unit total molecular gas (SFE mol ) is rather independent of the dense-gas fraction ( f dense ) that is measured with the J = 4−3 transition.…”
Section: The Relationships Between Star-formation Efficiency Dense-gsupporting
confidence: 86%
See 2 more Smart Citations
“…The lines in the plots are Local Polynomial Regression fits only to guide the eye, which is similar to the binning method used in many other studies, and they do not strongly suggest that our data points closely follow those fits. This is consistent with Usero et al (2015) and the larger galaxy sample compiled by Gallagher et al (2018a), where they show a very weak correlation (ρ sp = 0.13) and a large scatter about the relationships, and they suggest that the HCN/CO ratio is a relatively poor predictor of SFE mol . Our plot shows a similar case using high-J dense molecular lines, implying that the SFE, if measured as SFR per unit total molecular gas (SFE mol ) is rather independent of the dense-gas fraction ( f dense ) that is measured with the J = 4−3 transition.…”
Section: The Relationships Between Star-formation Efficiency Dense-gsupporting
confidence: 86%
“…This is likely due to our limited data for only one galaxy, and the variation of f dense is large, especially in the log 10 Σ stellar range between 2.5 and 3. If we compare our data points with previous studies (Gallagher et al 2018a;Usero et al 2015), they seem to lie in a similar range in the plot, though we are using high-J lines.…”
Section: The Relationships Between Star-formation Efficiency Dense-gsupporting
confidence: 53%
See 1 more Smart Citation
“…Momose et al (2010) measured the star formation efficiency (SFE = Σ SFR /Σ H 2 ) in a barred galaxy of NGC 4303 at a spatial resolution of 500 pc and reported that the SFEs in the arm regions are about two times higher than those in the bar regions (see also Yajima E-mail: fmaeda@kusastro.kyoto-u.ac.jp et al 2019). Such variations of the SFE with environments are reported for other nearby galaxies and the Milky Way (e.g., Watanabe et al 2011;Leroy et al 2013;Longmore et al 2013;Hirota et al 2014;Usero et al 2015;Gallagher et al 2018), but physical mechanism which controls the SFE within galaxies is still unclear.…”
Section: Introductionmentioning
confidence: 81%
“…A model of gas self-gravity and orbital motions throughout galaxies The cloud-scale measurements needed to examine how several of the parameters in our model of star formation are related and how they vary together throughout the disks of real star-forming galaxies, are currently being assembled by the PHANGS collaboration (A. K. Leroy et al, in prep. ; see also Gallagher et al 2018a;Sun et al 2018;Utomo et al 2018;Chevance et al 2019;P. Lang et al, ApJ subm.…”
Section: Bottleneck Using Semi-empirical Cloud and Galaxy Modelsmentioning
confidence: 94%